An Open Labelled Randomized Clinical Trial of Fluoxetine Versus Dapoxetine Treatment among Men with Premature Ejaculation and its Effect on Marital Satisfaction - Che Man, Mohammad; Mohd Zain, Faridah; Yaacob, Najib Majdi; Che Alhadi, Shahidah; Ismail, Shaiful Bahri (IIUM Medical Journal Malaysia, 2017)
Introduction: Premature ejaculation (PE) reduces sexual satisfaction and quality of life. Both SSRI Fluoxetine and Dapoxetine have been used in the treatment of PE. Fluoxetine is used as off-label treatment meanwhile Dapoxetine is the first SSRI specifically designed for PE with short half-life and few side effects. Objectives: To compare the PE symptoms and marital satisfaction score between Fluoxetine and Dapoxetine groups. Materials and method: In this clinical trial, 44 participants aged between 18 and 64 with PEDT score of ≥9 from the Primary Care clinic of Hospital USM, Kelantan were recruited and randomized into two groups; Fluoxetine Group(FG) and Dapoxetine Group(DG). They were prescribed with either daily oral Fluoxetine 20mg or Dapoxetine 30mg on demand twice weekly for 8 weeks. PE symptoms were measured using the Premature Ejaculation Diagnostics Tool(PEDT) score and marital satisfaction score were measured using the Dyadic Satisfaction-Dyadic Adjustment Scale(DS-DAS) score. Measurements were made at baseline and at the 8thweek(post intervention). Results: In FG and DG, 22 and 21 participants completed the study, respectively. PEDT scores reduced significantly within both groups[from 11.41 to 5.45(P<0.001) within FG and from 13.43 to 3.10(P<0.001) within the DG]. At the 8thweek follow-up, PEDT scores was observed to be were lower in DG(6.03 vs. 2.49,P<0.001) after adjustment of the baseline PEDT score. Significantly increased DS-DAS scores were observed in both groups [from 34.50 to 40.68(P<0.001) within FG and from 36.57 to 44.33,(P<0.001) within DG] with no significant difference in DS-DAS scores at the end of study(41.13 vs. 43.86,P=0.055) after adjustment of the baseline DS-DAS score. Conclusion: Reduction in PE symptoms was observed for both groups. At 8 weeks, PE symptoms among participants on Dapoxetine were significantly lower compared to the participants on Fluoxetine at 8 weeks. Treatment of PE with either Fluoxetine or Dapoxetine reduces symptoms of PE and improves marital satisfaction.